HAKIKAT PERNIKAHAN DALAM PANDANGAN HUKUM ISLAM - Suparman, Milda Nurjanah; Isnaini, Fajar; Nasrulloh, Adang Muhamad (Al-Usroh, 2024)
This article is motivated by a phenomenon that often occurs among Indonesian people, namely divorce. The causes that trigger divorce include a married couple lacking knowledge. Only capitalizing on love, not basing the family on religion. Lack of understanding, let alone living the essence, purpose and function of marriage. This is the origin of the marriage building which is currently fragile, barren and easily collapsed. It is easy for married couples to separate. The focus of the study in this article is more on the nature, purpose and function of marriage. Library research as a research method used is descriptive. So that this research is limited only to the activity of examining a collection of readings, both sourced from books, the internet and documents. The results show that the nature of marriage from an Islamic point of view is an act of worship for men and women who are ready so as to maintain dignity and honor. The nature of marriage as mentioned in the Qur'an is to bring peace and love (Arrum: 21). Married life is about mutual help and friendship ('Abasa: 36). The relationship between husband and wife is a relationship of leadership in serving and protecting. The purpose of marriage is to preserve the human species, sakinah mawaddah Warahmah. While the functions of marriage are biological, educational. recreation, affection, religious, socialization protection and economic.